Optimizing Loading/Unloading Processes for Sustainable Transportation Management - Sibarani , Mauritz Halomoan Manontang; Tampubolon, Brenhard Mangatur; Herawati, Susi (Jurnal Abdidas, 2024)
This research delves into the optimization of loading/unloading processes to reduce dwelling time and enhance supply chain sustainability in the transportation management domain. Through qualitative analysis and interviews with industry professionals, key strategies such as automation, standardized containerization, and improved scheduling techniques are explored to mitigate delays. Findings underscore the critical role of operational efficiency, environmental sustainability, industry needs analysis, professional standards, and international benchmarks in shaping a resilient and efficient transportation ecosystem. Insights gleaned from this study inform strategic decision-making and policy formulation aimed at fostering a more sustainable, efficient, and inclusive future for the global transportation community.